Human Resources Development Of Public Service Providers In Labuhanbatu Selatan Regency - Wildan Aswan Tanjung; Sampara Lukman; Khasan Effendy; Aries Djaenuri (GoAcademica Research & Publishing, 2020)
This study discusses the development of human resources of public service providers in Labuhanbatu Selatan Regency. The research is expected to provide an understanding of the current picture of ASN conditions and what strategies are taken by the local government of Labuhanbatu Selatan Regency to improve ASN competence. The method used in this study is a qualitative analysis method by collecting data by interviewing and collecting literature related to this research. The results showed that the development of resource competencies an Investment of the One-Stop Integrated Services Office still needs to be improved, primarily managerial and socio-cultural competencies. This development can be done by making a roadmap so that development can be carried out continuously.